In-situ anion exchange based Bi2S3/OV-Bi2MoO6 heterostructure for efficient ammonia production: A synchronized approach to strengthen NRR and OER reactions. (30th May 2022) - Zhang, Yuanyuan; Guo, Li; Wang, Yingxian; Wang, Tianyu; Ma, Taoxia; Zhang, Zhuangzhuang; Wang, Danjun; Xu, Bin; Fu, Feng
Highlights: The Bi2 S3 /OV-Bi2 MoO6 S-scheme heterojunction is constructed using a simple in-situ anion exchange process enabling oxygen vacancy (OV) abundant Bi2 MoO6 microspheres with surface deposited Bi2 S3 . The as-fabricated Bi2 S3 /OV-Bi2 MoO6 functioned as an effective photocatalyst to convert N2 -to-NH3 under mild conditions without any sacrificial agent. The photocatalytic NH3 production rate reached 126 μmol gcat −1 under visible light for 2.5 h with 2% Bi2 S3 /OV-Bi2 MoO6 photocatalyst, which was 8 fold higher than Bi2 MoO6 . The S-scheme heterojunction accelerated the e − / h + pairs spatial separation and accumulation on the Bi2 S3 and Bi2 MoO6 side, respectively, thus simultaneously strengthening both OER and NRR half-reactions. Abstract: Photocatalytic ammonia generation via nitrogen reduction reaction (NRR) is a green and prospective nitrogen fixation technique. However, NRR is often hampered by the high N2 adsorption/activation energies and is accompanied by a slow kinetics oxygen evolution reaction (OER). Herein, a robust Bi2 S3 /OV-Bi2 MoO6 S-scheme heterojunction is constructed using a simple in-situ anion exchange process, which enables oxygen vacancy (OVs) abundant Bi2 MoO6 microspheres with surface deposited Bi2 S3 . The as-fabricated Bi2 S3 /OV-Bi2 MoO6 functioned as an effective photocatalyst to convert N2 -to-NH3 under mild conditions. The photocatalytic NH3 /NH4 + production rate reached 126 μmol gcat −1 under visible light for 2.5 h with 2% of Bi2 S3 /OV-Bi2 MoO6 photocatalyst, which was 8-fold higher than pristine Bi2 MoO6 . Furthermore, the as-fabricated Bi2 S3 /Bi2 MoO6 heterojunction exhibited good selectivity, high stability and reproducibility. The excellent photocatalytic NRR performance was ascribed to the Bi2 S3 /Bi2 MoO6 heterojunction formed subsequent to the strong interaction between Bi2 S3 and Bi2 MoO6 . The OVs facilitated the chemical adsorption process allowing activation of N2 molecule on the Bi2 S3 /Bi2 MoO6 . Simultaneously, the S-scheme heterojunction prolonged the lifetime of photogenerated carriers, accelerated the electrons/holes spatial separation and accumulation on the Bi2 S3 (reduction) and Bi2 MoO6 side (oxidation), respectively, thus strengthening both OER and NRR half-reactions. This simple in-situ anion exchange method offers a novel technique for strengthening OER and NRR half-reactions in Bi-based photocatalysts for effective photocatalytic ammonia generation.